Nrf2 deficiency exacerbates ochratoxin A-induced toxicity in vitro and in vivo. (15th August 2017) - Loboda, Agnieszka; Stachurska, Anna; Sobczak, Mateusz; Podkalicka, Paulina; Mucha, Olga; Jozkowicz, Alicja; Dulak, Jozef
Abstract: Several mechanisms are postulated to be responsible for nephrotoxic and nephrocarcinogenic activities of mycotoxin and food contaminant, ochratoxin A (OTA). Although Nrf2 transcription factor was suggested to be involved in OTA–mediated renal injury, comprehensive study evaluating the effect of OTA toxicity in Nrf2 knock-out mice with special regard to sex-dependency has not been performed yet. Our results clearly show exacerbated OTA toxicity in porcine tubular epithelial cells after shRNA-mediated Nrf2 inhibition as well as in proximal tubular cells isolated from Nrf2 −/− male mice in comparison to cells derived from their wild-type counterparts. In vivo study revealed that male mice are significantly more susceptible to OTA-mediated injury than females and this effect was further enhanced in mice lacking Nrf2. OTA increased the expression of pro-fibrotic, pro-inflammatory and pro-apoptotic factors, while concomitantly decreased the level of claudin-2 and vascular endothelial growth factor (VEGF). Importantly, miR-21, mi R -34a and mi R -382 were potently up-regulated after OTA delivery. Noteworthy, treatment with sulforaphane (SFN), diminished expression of OTA-induced inflammatory cytokines (IL-1β, IL-6), pro-apoptotic factors (c-myc, PUMA) and microRNAs (mi R -382, mi R -34a) in male mice. In summary, our data implies sex-dependent effect of OTA, with males being more sensitive. The lack of Nrf2 enhances susceptibility to mycotoxin-induced pathologies, suggesting that modulation of the Nrf2 pathway may provide a therapeutic approach to treat OTA-triggered renal diseases.